How Do the Political Parties Survive? Case Study on the Private Financing of Political Parties in Romania - Cornea, Valentina; Mirică, Ștefania Cristina; Ungureanu, Ecaterina Cornelia; Moga, Liliana Mihaela; Mihalache, Andi (Acta Universitatis Danubius. Œconomica, 2022)
In the present paper we aim to analyze several important aspects regarding the methods in which political parties obtain their finances and to present the amounts and the private financial sources of Romanian parliamentary political parties in the last legislature (2016-2020). Political parties are necessary elements for any democratic society. The exercise of fundamental human rights is only possible in democracies and democracies require a group of representatives in order to govern the society. The political parties provide these representatives and, there for, the good functioning of political parties is essential in a democratic society. In the present paper we discuss the financial resources of political parties, and the Romanian legal provisions in this matter and also, we will present and analyze data regarding the financing of parties. The political parties are financed by the state and also have private resources like: membership fees, donations, loans and other resources. In our case study we referred to the case of Romania, more specifically of the amount of financing the parliamentary political parties in the 2016 – 2020 legislature. The method used is scientific research and data analysis.